Macmillan English Thinking and Writing Processes - Laidlaw, Scribner (London Collier Macmillan Publishers, 1988)
Macmillan English makes solid connections between the processes that underline good writing. Every stage of the writing processes prewriting, writing, revising involves thinking. Writing is thinking made visible. Grammar provides a useful structure for olderly thinking about words.
Keywords: English Practice